2020
DOI: 10.1002/ejp.1614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a person‐centred approach in a school setting for adolescents with chronic pain—The HOPE randomized controlled trial

Abstract: BackgroundChronic pain among adolescents is common but effective interventions applicable in a school setting are rare. Person‐centred care (PCC) is a key factor in improving health by engaging persons as partners in their own care.MethodsIn this randomized controlled trial, a total of 98 adolescents in secondary school or upper secondary school (aged 14 − 21 years) with chronic pain were randomly assigned to a PCC intervention or standard school healthcare. In the intervention group a pain management programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 53 publications
1
22
0
2
Order By: Relevance
“…They are mostly used to relax and soothe people, to give constant comfort, to soothe hurts and to give people positive strength [ 6 ]. The reasons why the “healing boom” is in full swing in China are similar to the context in which it arose in Japan [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are mostly used to relax and soothe people, to give constant comfort, to soothe hurts and to give people positive strength [ 6 ]. The reasons why the “healing boom” is in full swing in China are similar to the context in which it arose in Japan [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Principle 3 furthermore stipulates that design should provide effective prompting and feedback during and after task completion (Table 1). This aligns to ‘the story’ and ‘the documentation’, which are key concepts of person‐centred care for children (Britten et al, 2017; Ekman et al, 2011; Fors et al, 2020). The interviews clearly showed that this was the case, and that healthcare practitioners, parents and children experienced that the children's participation increased – both before, during and after the hospital visit.…”
Section: Discussionmentioning
confidence: 56%
“…The practitioners at the child psychiatry clinic also believed that the provision of communication material with pictures, which could be taken home and used there, could make parents more active and children more involved, even after the visit to the clinic. It is important for everyone to talk and discuss the visit, as this constitutes a basic element in person‐centred care processes, namely creating one's personal story (Britten et al, 2020; Fors et al, 2020). Person‐centred paediatric care invites the child into the process of decision‐making and negotiating of care, and researchers argue that universal access to pictorial support and possibly other supportive tools may be necessary to involve children in person‐centred care (Carter & Ford, 2013; Nilsson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations